33 THE DOCUMENTARY HISTORY OF THE RATIFICATION OF THE CONSTITUTION 739 (John Kaminski et al. eds., 2019). - (:unkn) unknown (My University, 1787)
Ordered the collection of all public arms to have them repaired in Philadelphia.
Keywords: POSSESSION